The Role of Legal Pluralism in the Peacebuilding Process - Yan, Cassadee Orinthia; Benhima, Mohamed (The international journal of interdisciplinary global studies, 2025)
The role of legal pluralism in the peacebuilding process has been a subject of debate from national and international perspectives. Taking the case of East Timor, the article starts with the country’s independence struggle and the challenges and prospects that followed. The article defines and studies legal pluralism’s theoretical foundations, exploring East Timor’s various legal systems and their interactions. It underscores legal pluralism’s importance in fostering inclusive governance, resolving historical grievances, promoting social cohesion, and embracing diversity. The article goes on to examine the integration of customary law into legal frameworks, the acknowledgment and integration of minority rights and perspectives, and the enhancement of local governance structures and community involvement. Moreover, it delves into the significance of transitional justice processes and the role of legal mechanisms in truth-telling and accountability. The issues posed by potential disagreements across official and unofficial legal systems, along with the dynamics of power and gender within legal pluralism, are acknowledged in the article. It emphasizes the necessity of legal reform, capacity development, and finding a harmonious equilibrium between individual rights and communal interests. Moreover, the article offers concrete instances of legal pluralism at work in East Timor and draws comparisons with other post-conflict situations.